Evaluasi Destinasi Wisata Terbaik di Indonesia Dengan Kombinasi Metode ARAS dan AHP - Firmansyah, Ariq; Susanto, Bagus Hadi; Pinem, Agusta Praba Ristadi (Forum Kerjasama Pendidikan Tinggi, 2024)
The management of tourist destinations in Indonesia strives to enhance the quality and comfort for tourists by considering safety aspects. To evaluate the best tourist destinations based on safety and comfort criteria, this study applied a decision support system using the Analytical Hierarchy Process (AHP) to calculate the weights of each safety criterion, including visitor insurance, safety and security procedures, standard operating procedures, tourism business certification, the number of destinations, and operational permits. The Additive Ratio Assessment (ARAS) method was then used to rank tourist destinations based on the calculated weights. The results of the AHP method provided accurate priority weights, while the ARAS ranking positioned Central Java (A3) as the highest-ranked destination with a score of 0.956, followed by Jakarta (A1) with a score of 0.897, and Yogyakarta (A4) with a score of 0.840. A Spearman correlation test between the AHP-ARAS ranking and visitor numbers resulted in a coefficient of 0.857 with a p-value of 0.014, indicating a very strong and statistically significant positive relationship. This study provides valid recommendations for tourists and decision-makers in selecting tourist destinations that align with prioritized safety criteria, while also supporting the development of data-driven and objective tourism management policies.